De(s) patients détenus. Se soigner dans un environnement contraignant - Lara Mahi (Anthropologie & Santé)
This article focuses on three reasons which limit the emergence of a 'contemporary patient' in the sanitary units of prisons: the inmates/patients do not make appointments with healthcare professionals but instead are summoned by them, they are denied access to certain types of documents and information, and they can only count on limited social support to elaborate their view of their illness. Nevertheless, this constraining and disempowering system rarely leads to a disengagement from medical services. Instead, most of the sick inmates take the opportunity, during their incarceration, to seek support. This article aims to show that the motivation of their personal involvement is not necessarily to seek care but sometimes to be part of what Goffman calls a 'privilege system'.